TAp63 regulates bone remodeling by modulating the expression of TNFRSF11B/Osteoprotegerin. Issue 22 (17th November 2021) - Lena, Anna Maria; Foffi, Erica; Agostini, Massimiliano; Mancini, Mara; Annicchiarico-Petruzzelli, Margherita; Aberdam, Daniel; Velletri, Tania; Shi, Yufang; Melino, Gerry; Wang, Ying; Candi, Eleonora
ABSTRACT: The transcription factor p53 has been shown to control the differentiation process of the mesenchymal stem cells (MSCs). As a matter of fact, in vivo p53 loss leads to an unbalance between bone formation versus bone erosion. Using as experimental system, human bone marrow-derived MSCs and mouse bone marrow-derived TAp63-/- MSCs, we have asked whether the other members of the p53 family, p63 and p73, are involved in controlling MSCs osteogenic differentiation. Our results indicate that both during human and mouse MSC-induced osteogenic differentiation, TAp63 isoforms are mainly upregulated in comparison with p73 isoforms. In addition, MSCs derived from TAp63 knock-out mice show delayed osteogenic differentiation. Interestingly, we found that, in contrast to p53, TAp63 trascriptionally regulates osteoprotegerin (OPG or TNFRSF11B) important for bone remodeling and osteoclastogenesis inhibition throughout the RANKL/RANK/OPG pathway. Analysis of the expression of p63 and OPG in breast cancer, which is one of the most common human cancers that metastatizes to bone, showed that p63/OPG pathway is deregulated and that a higher expression of both p63 and OPG is associated with a better patient survival, suggesting that p63/OPG axis may be further investigated as clinical biomarker for breast cancer metastasis. Abbreviations: MSC, mesenchymal stem cells; OPG, osteoprotegerin; RUNX2, Run-trelated transcription factor 2